2005
DOI: 10.1097/00149831-200506000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low-frequency electrical myostimulation and conventional aerobic exercise training in patients with chronic heart failure

Abstract: In patients with moderate to severe CHF, 5 weeks of EMS and conventional exercise training produce similar improvements to exercise capacity and muscle performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 29 publications
5
43
1
6
Order By: Relevance
“…This was the first study to demonstrate that skeletal muscle electrical stimulation regimens can attenuate the production of cardiovascular inflammatory mediators and exert beneficial effects on endothelial dysfunction in patients with heart failure. However, in accordance with the studies of Harris et al [98] and Nuhr et al [99] and unlike the studies by Maillefert et al [94], Vaquero et al [95] Deley et al [100] and Dobsȃk et al [102], the investigators reported no significant differences in peak oxygen consumption after the completion of the protocol.…”
Section: Functional Electrical Stimulation and Heart Failuresupporting
confidence: 78%
See 1 more Smart Citation
“…This was the first study to demonstrate that skeletal muscle electrical stimulation regimens can attenuate the production of cardiovascular inflammatory mediators and exert beneficial effects on endothelial dysfunction in patients with heart failure. However, in accordance with the studies of Harris et al [98] and Nuhr et al [99] and unlike the studies by Maillefert et al [94], Vaquero et al [95] Deley et al [100] and Dobsȃk et al [102], the investigators reported no significant differences in peak oxygen consumption after the completion of the protocol.…”
Section: Functional Electrical Stimulation and Heart Failuresupporting
confidence: 78%
“…A more recent study by Deley et al [100] compared the effects of low-frequency electrical stimulation and conventional exercise training in 24 patients with stable CHF and NYHA grades II and III. The patients underwent 5 weeks of exercise training, 5 h per week, using FES (a low-frequency 10-Hz biphasic current delivered to both quadriceps and clf muscles) or conventional training programs (three 20-min periods of different aerobic exercises, i.e., treadmill, bicycle, arm cycling, with a global warm-up and cool-down).…”
Section: Functional Electrical Stimulation and Heart Failurementioning
confidence: 99%
“…Muscle strength, assessed by isometric and isokinetic dynamometry, increased significantly in all subjects, which concords completely with similar clinical reports, highlighting the positive effects of chronic LFES against skeletal muscle atrophy and in enhancing muscle power in these patients. [29][30][31] In the present study, the increase in maximal muscle strength was achieved with a frequency of 10 Hz, although Quittan et al 30,31 reported an increase in muscle strength using a frequency of 50 Hz.…”
Section: Discussioncontrasting
confidence: 54%
“…NMES delivered at a frequency of 50 Hz and an amplitude chosen to induce muscle contractions at 25-30% of maximal voluntary contraction induced significant increases in the strength and cross-sectional area of the thigh muscles in CHF patients awaiting heart transplantation [38]. Subsequently, additional studies have confirmed the benefits of NMES in CHF patients [39,40].…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 98%